Multinational Corporations and the Development of Oil Bearing Communities in Imo State, Nigeria: Addax Petroleum Development Nigeria Ltd. in Perspective - OPARA, Ikechukwu Jonathan; EZIKEUDU, Chukwudi Charles; ETENG, Felix Onen; OKORIE, Chimaobi; NZEWI, Blessing Nzubechukwu; AKWAJI, Fidelis Ngaji; UZOMBA, Chigozie Ikechukwu; EJA, Terrence Richard; UQUETAN, Uquetan Ibor; EDET, Francis Felix; ISOKON, Brown; IWUCHUKWU, Goodluck Ndubuisi (Journal of Ecohumanism, 2024)
It is quite appalling that an oil rich environment is suffering from penury amidst abundance of wealth due to negligence. This research examined the contributions of Addax Petroleum Development Nigeria Ltd towards human capacity development and healthcare delivery in Imo State oil bearing communities. The study anchored on Samuel Huntington’s modernization theory. This work adopted mixed research design. The population of the study was fifty thousand while two thousand five hundred sample size was selected. The study employed Questionnaire, observation, interview and documentary methods of data collection. Simple percentage, Kearl Pearson correlation, analysis of variance (ANOVA) and regression analysis were employed for data analysis. The study discovered that Addax Petroleum Development Nigeria Ltd has contributed significantly towards human capacity development but has not impacted positively on healthcare delivery in the study area. The study recommended that multinational companies operating in Imo State oil bearing communities should as a matter of urgent concern contribute or donate appreciable resources towards healthcare needs of their host communities, so as to cushion the negative impact of petroleum production in their environment. This can be achieved by devoting two percent of their annual profits generated from the study area to healthcare needs of the inhabitants